The evolving regulatory system of advanced therapy medicinal products in China: a documentary analysis using the World Health Organization Global Benchmarking Tool standards - Shi, Junnan; Chen, Xianwen; Hu, Hao; Ung, Carolina Oi Lam (Cytotherapy (Oxford, England), 2024)
Advanced therapy medicinal products (ATMPs) are rapidly evolving to offer new treatment options. The scientific, technical, and clinical complexities subject drug regulatory authorizes to regulatory challenges. To advance the regulatory capacity for ATMPs, the National Medical Products Administration in China made changes to the drug regulatory system and developed regulatory science with the goal of addressing patient needs and encouraging innovation. This study aimed to systematically identify the regulatory evidence on ATMPs in China under the guidance of an overarching framework from the World Health Organization Global Benchmarking Tool. It was found that China's administrative authorities at all levels have issued a number of policy documents to promote the development of ATMPs, covering biopharmaceutical products research and development (n = 14), biopharmaceutical industry development (n = 9), high-quality development of medical institutions (n = 1), specific development plans/projects (n = 6) and specific regional development (n = 4). The legal and regulatory framework of ATMPs in China has been established and is subject to continuous adjustment in various aspects including regulations (n = 3), departmental rules or administrative normative documents (n = 22), and technical guidance (n = 15). As the regulatory reform continues, the drug review processes have been revised, and various technical standards have been launched, which aim to establish a regulatory approach that oversees the full life-cycle development of ATMPs in the country. The limited number of investigational new drug applications and approved ATMPs suggests a lag remains between the translation of advanced therapeutic technologies into clinically available medical products. To accelerate the translational research of ATMP in countries such as China, developing and adopting real-world evidence generated from clinical use in designated healthcare facilities to support scientific decision-making in ATMP regulation is warranted. The enhancement of regulatory capacity building and multi-stakeholder collaborations should also be encouraged to facilitate the timely evaluation of promising ATMPs to meet more patient needs.